Pencegahan Penularan Covid-19 Pada Balita Dan Anak Pra Sekolah Di Desa Pulo Lor - Septi Fitrah Ningtyas; Mudhawaroh; Dwi Sri Rahandayani; Nur Laila Faizah; Niken Grah Prihartanti (Puslitbang Sinergis Asa Professional, 2022)
COVID-19 is a new disease due to a virus that has not yet been identified. Services due to Large-Scale Social Restrictions which hinder population mobility. This can disrupt the continuity of health services which can lead to an increase in morbidity and mortality, especially in infants. The purpose of carrying out this dedication to the community is to disseminate guidance to increase children's immune energy so that they can avoid the transmission of COVID-19 transmission in infants and preschoolers. Providing data on methods of preventing the transmission of COVID-19 to infants and pre-school children is a strategy tried in Pulo Lor Village to avoid the transmission of COVID-19 in this age group. This training uses posters and direct descriptions as the method. Experiencing the COVID-19 pandemic, residents must be disciplined and practice cleanliness and live a healthy life. In order to help residents be more socialized, health workers coordinate matters relating to efforts to prevent the spread of COVID-19 and monitor the health of infants and preschool children. Finally, the method of protecting children's health goes hand in hand with efforts to prevent the transmission of COVID-19 to infants and preschoolers. If children need monitoring or bonus services, health service providers must provide telephone numbers or data lines that are ready to contact residents for consultations via telephone or appointments. It is hoped that by distributing counseling about methods of preventing the transmission of COVID-19 to infants and pre-school children in Pulo Lor Village, the dedication of these residents can increase family understanding of the disease, especially among mothers, without causing panic.